(2+1)(2的平方+1)(2的3次方+1)(2的4次方+1)(2的5次方+1)……(2的n次方+1) 怎么计算?

问题描述:

(2+1)(2的平方+1)(2的3次方+1)(2的4次方+1)(2的5次方+1)……(2的n次方+1) 怎么计算?
运算过程要有

(2+1)(2的平方+1)(2的3次方+1)(2的4次方+1)(2的5次方+1)……(2的n次方+1)
=2(3+1)(3^2 +1)(3^4 +1)(3^8 +1)(3^16+1)(3^32 +1).(3^2n+1)
=(3-1)(3+1)(3^2 +1)(3^4 +1)(3^8 +1)(3^16+1)(3^32 +1).(3^2n+1)
=(3^2-1)(3^2 +1)(3^4 +1)(3^8 +1)(3^16+1)(3^32 +1).(3^2n+1) 注释:用的是平方差公式(a+b)*(a-b)=a^2-b^2
=(3^4-1)(3^4+1)(3^8+1)(3^16+1)(3^32+1).(3^2n+1)
=(3^8-1)(3^8+1)(3^16+1)(3^32+1).(3^2n+1)
=(3^16-1)(3^16+1)(3^32+1).(3^2n+1)
=.
=(3^2n-1)(3^2n+1)
=3^4n-1